OP64 Examining patient-reported barriers to talking about advance care planning (ACP) with family physicians: a multi-site survey. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Tan, A; Bernard, C; Slaven, M; Howard, M; Elston, D; Heyland, D
Abstract : Background: Advance care planning (ACP) can improve satisfaction with end-of-life care among patients and families and reduce unwanted treatments. Primary care is an ideal setting in which to facilitate ACP. This study analyzed the reasons why patients find it difficult to discuss ACP with their family physicians. Methods: A self-completed, validated questionnaire about four ACP engagement behaviours and barriers was administered to patients aged 50 and older in 20 family practices in Canada. The questionnaire included an open-ended question about what makes it difficult to talk about ACP with the family physician. Four authors analysed the open-ended comments using thematic content analysis. Results: 810 patients (mean age=66, 55.6% female) participated. Of the 53% (n=428) of patients who had talked to someone about end-of-life medical treatments, only 18% (n=75) had talked with their family physician. Patients identified the following barriers to ACP conversations: 1) They feel too young, healthy and well; 2) They abdicate responsibility to their physician; 3) They worry about a negative impact of ACP on the physician relationship; 4) Inadequate time during appointments; 5) They feel ACP is emotionally difficult to discuss with their physician. Conclusions: Our findings suggest that patients need help preparing for ACP conversations, both to change the perception that ACP conversations only occur at the end-of-life and to normalize these discussions between patients and physicians. There is an opportunity for family physicians, who have longstanding relationships and frequent visits with patients, to have ACP conversations.